Women and Coffee Farming: Collective Consciousness towards Social Entrepreneurship in Ulubelu, Lampung - Dian Karinawati Imron; Al Rosyid Anggi Satrya (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Women and coffee farming raise close attention in agriculture and development debates. History shows that women profoundly contribute to producing good quality coffee. However, their involvement has not fully brought positive development for themselves and their families. As a major coffee producer, women in Ulubelu, Lampung experience that condition. Women face market uncertainty, lack access to knowledge, lack power to make decisions, face unsupportive policies, and experience low participation in organizations to gain capacity building on coffee value chain. Although women deal with the difficult situation, there are some figures that encourage collective reflection of women to address the coffee farming problem. This paper attempts to assess women’s consciousness of coffee farming and how they develop kinds of action through social entrepreneurship to tackle the coffee farming issues. The research used descriptive analysis with a case study approach. The study found various reflections as a sign of women’s consciousness to engage in coffee farming and value chain. There are: a) coffee as a source of farming livelihood, b) coffee as cooperative entrepreneurship, and c) coffee as a sustainability ideal. The consciousness drives women to act and makes positive change. Furthermore, there are diverse actors engaged; for instance, NGO (Non-Government Organization), states and private. Although there are many actors involved, the certain quality assistance needs to be improved.